The Relationship of Parent Parenting Patterns with Learning Achievement Students at SMK GKPS I Pematang Raya, Simalungun Regency - Jumadiah Wardati; Nadia Nahda Nasution; Ayu Sintya (PT Inovasi Pratama Internasional, 2022)
Parenting is the way or attitude of parents in raising and educating their children to behave in a healthy life. Parenting styles applied by parents are democratic, authoritarian, and permissive parenting styles. Learning achievement is the average value of the students' final semester exam results. The aim of the study was to identify the relationship between parenting style and student achievement at GKPS I Pematang Raya Vocational School, Simalungun Regency. This study uses a correlation descriptive research design. The population in this study were students at SMK GKPS I Pematang Raya, Simalungun Regency, class XI, namely 100 people. The number of samples obtained based on the calculation is 50 students. The sampling technique uses a simple random sampling approach. The research instrument consisted of 3 types of questionnaires: student demographic data, parenting patterns and learning achievement. To assess the strength of the relationship between parenting style and academic achievement, the Pearson correlation test was used. The results showed that 31 respondents (62%) were categorized as good parenting parents, and almost all respondents were in the moderate learning achievement category, namely 43 respondents (86%). Parenting style has a positive and adequate relationship with student achievement at SMK GKPS I Pematang Raya, Simalungun Regency, with a significant value of 0.000 (p <0.05), so it can be concluded that there is a relationship between parenting style parents with student achievement at SMK GKPS I Pematang Raya, Simalungun Regency. The research results obtained can be used as basic data and information for further research and it is recommended to pay more attention to data collection methods so that the data obtained is more accurate and representative.